Anthropometry correlation towards archery performance - Rabiu Muazu, Musa; Zahari, Taha; Anwar, P. P. Abdul Majeed; Mohamad Razali, Abdullah (Springer Singapore, 2019)
This chapter assesses the association of a selection of anthropometry parameters in identifying HPA and LPA. It was shown that the selected parameters, i.e. abdominal circumference, arm span, calf circumference, height, hip circumference, thigh circumference and weight, are essential in the identification of potential of the archers. Furthermore, it was demonstrated that the linear SVM variation model provided the best prediction capability amongst the other evaluated SVM models.